ANALISIS SEMIOTIKA ROLAND BARTHES PADA IKLAN COCA-COLA CHANGE HAS A TASTE - كوكا كولا- للتغييرطعم/ COCA-COLA LITTUGAIRI AT- TA’AM - Fadillah Shela Putri; Fatimatuzzahra Nasution; Aisyah Nabila; Wahyu Ramadani; Aulya Raudhoh Ritonga (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
This study aims to analyze the Coca-Cola Change Has a Taste advertisement using Roland Barthes' semiotic approach, with the objective of uncovering the denotative, connotative, and mythical meanings within the advertisement. This research is based on the phenomenon of advertisements not merely functioning as promotional tools but also serving as communication media that convey social and cultural messages. The one-minute-and-six-second advertisement, published on YouTube by Coca-Cola Middle East, presents a narrative that represents social issues in the context of Middle Eastern culture. The study employs a qualitative approach with a descriptive method, aiming to systematically describe the visual elements, text, and monologue. The data were analyzed using Roland Barthes' semiotic theory, which involves the stages of sign identification, meaning classification, and cultural context interpretation. The findings reveal that, at the denotative level, the advertisement depicts scenes reflecting daily routines, such as a father teaching his daughter to drive, set against a desert backdrop with traditional cultural elements. At the connotative level, the advertisement emphasizes messages of social transformation, particularly women's empowerment, along with symbols of a modern lifestyle. At the mythical level, the narrative conveys the integration of tradition and modernity, aligning with the vision of social transformation promoted by Saudi Arabia's Vision 2030. The study concludes that the Coca-Cola Change Has a Taste advertisement not only promotes the product but also constructs a narrative that reflects social change and the relationship between globalization and local identity.